Perancangan Sistem Informasi Pelayanan Organisasi Kemahasiswaan Universitas Teknologi Akba Makassar (Unitama) Berbasis Web - Maulidinnawati, Andi; Syamsu, Suryadi; Tamrin, Fadli; Arafah, Muhammad; Yusuf , Andi M; Maslihatin, Tatik; Sumardin, Andi; Pasnur, Pasnur; Resha, Muhammad; Fauziah Suhardi , Rifdah Tami (JNSTA ADPERTISI JOURNAL, 2022)
The campus has an organization to develop the potential of its students according to the student division therefore This study aims to create a web-based service information system for student organizations in order to facilitate the service and implementation of procedures for submitting proposals and activity reports. The data were obtained through observations, Correspondence documents, direct interviews with the campus and organizational management. This system is built using visual studio code and mysql as a database storage service. The system development method in this research uses the waterfall method with the stages, namely analysis, design, coding, testing and implementation (maintenance programs). The results of this study indicate that the student organization service information system can run well. Based on the results of testing using blackbox testing techniques obtained 81% results from respondents, so it is said to be suitable for use based on the tests carried out.